1990
DOI: 10.3354/meps066095
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable invasion of San Francisco Bay (California, USA), by the Asian clam Potamocorbula amurensis. II, Displacement of a former community

Abstract: Long-term macrobenthic sampling at a site in northern San Francisco Bay has provided an unusual opportunity for documenting the time course of an invasion by a recently introduced Asian clam Potamocorbula arnurensis. Between 1977, when sampling began, and 1986, when the new clam was first discovered, the benthic commun~ty varied predictably in response to river inflow. During years of normal or high river inflow, the community consisted of a few brackish or freshwater species. During prolonged periods of low r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
110
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(123 citation statements)
references
References 4 publications
(7 reference statements)
3
110
1
1
Order By: Relevance
“…Competition in particular is increasingly recognized as a major means through which non-indigenous species have an impact on native species (Nichols et al 1990;Byers 2000). From this study and that by Muller (2001), it appears that P. gibbesi and P. marmoratus are potential competitors for space Á and according to Muller (2001), also for food Á since the two species have been observed to occur in close proximity.…”
Section: Discussionsupporting
confidence: 48%
“…Competition in particular is increasingly recognized as a major means through which non-indigenous species have an impact on native species (Nichols et al 1990;Byers 2000). From this study and that by Muller (2001), it appears that P. gibbesi and P. marmoratus are potential competitors for space Á and according to Muller (2001), also for food Á since the two species have been observed to occur in close proximity.…”
Section: Discussionsupporting
confidence: 48%
“…The recent colonization and domination of the SFE benthos by Corbula amurensis Schrenck, 1861 (the Asian overbite clam) (Feyrer et al 2003;Cloern and Jassby 2012) has displaced many of these prey species (Nichols et al 1990;Gilbert et al 2011;Greene et al 2011;Cloern and Jassby 2012). Other sturgeon species have been shown to successfully adjust their diet to altered prey availability (Brosse et al 2000;Usvyatsov et al 2012), and the Asian overbite clam has been identified as a major component of the diet of the sympatric white sturgeon (Kogut 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The catastrophic ecological impacts of introduced species such as the Asian clam Potamocorbula amurensis in San Francisco Bay (Nichols et al 1990) and the comb jelly Mnemiopsis leidyi in the Black Sea (Shushkina & Musayeva 1990) have highlighted the significance of introduced species in the marine environment (including bays, estuaries, and open coasts). Although there has been a rapid increase in the study of the ecological consequences of marine invasions in the past decade (e.g.…”
Section: Introductionmentioning
confidence: 99%